The effects of magnesium L-threonate (Magtein®) on cognitive performance and sleep quality in adults: a randomised, double-blind, placebo-controlled trial - Lopresti, Adrian L.; Smith, Stephen J. (Frontiers in Nutrition, 2026)
Background/objectivesMagnesium may help support cognition and sleep. The purpose of this two-arm, 6-week, parallel-group, randomised, double-blind, placebo-controlled trial was to examine the effects of magnesium L-threonate (Magtein®) supplementation on cognitive performance, cognitive age, sleep quality, and selected physiological indicators in adults.MethodsOne hundred adults aged 18 to 45 with self-reported dissatisfied sleep were supplemented with 2 g daily of Magtein® or a placebo. Outcome measures comprised the computer-based National Institute for Health (NIH) Cognitive Toolbox and Raven’s Progressive Matrices Version 2 for the assessment of cognitive function, self-report evaluations of sleep quality and emotional wellbeing, a reaction time test, and physiological data obtained from a sleep-tracking wearable device (Oura Ring), including resting heart rate (HR) and heart rate variability (HRV) during sleep.ResultsCompared to the placebo, Magtein® was associated with greater improvements in overall cognitive performance as measured by the NIH Total Cognition Composite (p = 0.043), with larger treatment effects on working and episodic memory. There was also a 7.5-year reduction in estimated brain cognitive age and a greater improvement in reaction time (p = 0.031). However, there were no group differences in changes in the Raven’s test (p = 0.953). Based on self-report measures, there was a greater improvement in sleep-related impairment (p = 0.043), but no group differences in changes in sleep disturbances (p = 0.316), restorative sleep (p = 0.439), or general wellbeing (p = 0.436); although in a subset of participants with more severe sleep-related problems, group differences in sleep-disturbances were identified (p = 0.031). Based on data from the sleep tracking ring, there were no group differences in sleep outcomes, although there was a greater reduction in HR (p = 0.030) and an increase in HRV (p = 0.036), a physiological marker of stress reduction and improved autonomic balance. Magtein® was well-tolerated, and there were no reports of significant adverse reactions.ConclusionThe results from this study suggest Magtein® supplementation for 6 weeks improves overall cognition, cognitive age, working memory, reaction time, HR, HRV, and some subjective, but not objective measures of sleep in healthy adults with self-reported dissatisfied sleep.